Intercultural Dialogue in the European Education Policies A Conceptual Approach - Lähdesmäki, Tuuli (Springer Nature, 2020)
This open access book analyses intercultural dialogue as a concept, policy and ideal in European education policy documentation. The core European transnational organizatons - the Council of Europe and the European Union - have actively promoted policies to engender inclusive societies and respond to challenges that diversification may entail. This book, in turn, offers suggestions for improving education policies in super-diversified Europe and beyond, where there is an increasing need for cultural understanding and constructive dialogue. The authors utilize concept analysis to reveal how these organizations seek to deal with dialogue between cultures, as well as weight given to cultural differences and intercultural encounters. This book will be of interest and value to scholars of intercultural dialogue and European education policies.